Company Debt Policies Across Different Tax Rate Structures - Myers, Jedd (My University, 2012)
Managers deciding which form of finance to select in order to fund investments, namely debt or equity, are posed with the challenge of understanding the different costs implicated with these two types of financing. Equity investors expect far greater returns than lenders of debt, yet repayment of their investment is more flexible. Debt is associated with stringent repayment terms, yet the tax benefits of this source of finance are material. The ultimate decision rests on the returns to the shareholders, which are increased with higher debt levels due to the concept of gearing of returns. This research report investigates the tendency of managers to exploit the tax benefits offered by debt in a range of different tax rates as well as different interest rates. These are the two factors which impact on the tax benefits offered by debt financing. Capital structure data has been collected from selected stock exchanges and central banks. This data has been used in multiple regression analyses where debt levels have been regressed against tax and interest rates in order to determine the impact of these variables on debt funding levels. The results show that when countries are grouped geographically, there is no correlation between changes in financing behaviour and tax rate changes. However, when countries are grouped according to tax rate brackets, more significant connections may be observed. The relationship between financing decisions and changes in interest rates also proved more significant throughout the report. The report demonstrates that financing decisions change in relation to tax rate changes and highlight the tax benefits of debt financing.
MBA thesis - WBS
Keywords: Company debt policies; Debt; Taxation; Debt financing